A Questionnaire-Based Study on Medicinal Plant Use in Patients with a Chronic Disease Diagnosis - Bahar Gürdal; Ebru Yesin (Tehran University of Medical Sciences, 2022)
Chronic diseases are the most common non-communicable diseases worldwide. Today, with the increase in the elderly population, the burden of the disease is gradually increasing, and alternative treatment methods for these diseases are gaining importance. Potential adverse reactions, contraindications, and interactions with prescription drugs and herbals are important to evaluate. Therefore, the use of plants by chronic patients should be under supervision of health professionals. In this study, we aimed to obtain comprehensive data by questioning the plants used by patients using drugs for chronic disease, their usage patterns, and changes seen as a result of plant use. For this purpose, 60 people over the age of 18 (47% female, 53% male) participated in the survey study, and 53.3% of the patients stated that they used plants in the treatment. Twenty-one plants have been identified. Linden and mint-lemon mixture are the most commonly used plants, accounting for 62% and 15% of the total, respectively. The most commonly used preparation method is decoction (60%). 62.5% of the users obtain the plants from herbalists' stores; 59.37% of the patients learned the use of plants through advice (friend, neighbor, relative); 96.87% of the patients stated that they benefited from the use of plants. According to these results, the patients need to be informed about the use of plants as a complementary treatment. Thus, further efforts should be made to raise awareness of the use of herbal medicine and possibility of herb-drug interactions among physicians and other health professionals.